Responsive Web Design Learning Media: Enhancing Student Independence in Vocational Web Programming - Yoga, Wira Tri; Kusumadyahdewi, Kusumadyahdewi; Utomo, Wahyu Mulyo (Universitas Negeri Malang, 2023)
The main objective of this learning media development is to develop Responsive Web Design (RWD) based learning media with Pomodoro learning technique on web programming. The learning media is used to create learning media that is not monotonous, and students can learn independently with features such as Pomodoro time management, monitoring material that has been learned, live coding to learn coding practices, and quizzes to monitor student understanding. This research and development uses the Plomp development model reference which consists of 5 stages, namely (1) preliminary investigation, (2) design phase, (3) realization/construction phase, (4) test, evaluation, and revision phase, and (5) implementation phase. Products that have been produced in the form of Responsive Web Design (RWD) learning media with the name WCode. The results of the material expert validation assessment were 78.87 percent, media validation was 92.71 percent, development trials (small groups) were 87.36 percent, field trials (large groups) were 90.02 percent, the level of student learning independence after using the media was 79.38 percent with an increase of 12.99 percent from the level of student learning independence before using the learning media made. Overall, the learning media made can be considered feasible and used as a means of student learning materials in class and supporting independent student learning on web programming elements for vocational students majoring in Software Engineering.